Il divo der Göttliche - Sorrentino, Paolo 1970-; Bigazzi, Luca 1958-; Servillo, Toni 1959-; Bonaiuto, Anna 1950-; Bosetti, Giulio 1930-2009 (EuroVideo Bildprogramm GmbH, 2008)
The story of Italian Prime Minister Giulio Andreotti, (who has been elected to Parliament seven times since it was established in 1946) and the controversial associations he had with both the Mafia and the Catholic Church
Original: Italien, Frankreich 2008
Keywords: Andreotti, Giulio; Andreotti, Giulio -- 1919-2013; Geschichte; Political corruption / Italy / Drama; Mafia / Drama; Organized crime / Drama; Mafia -- Drama; Organized crime -- Drama; Political corruption -- Italy -- Drama; Mafia; Korruption; Italien; Film; DVD-Video